Penerapan Model Inkuiri Terbimbing Untuk Meningkatkan Penguasaan Materi Energi - Belseran, Jilyen Patricia; Malawau, Seska; Latupeirissa, Asry N. (Pattimura University, 2024)
This research aims to determine the increase in mastery of Energy material by implementing a guided inquiry model for class VIII students at SMP Negeri 60 Central Maluku. This type of research is descriptive quantitative, with a one-group pretest-posttest design. Research subjects are people who provide information regarding the data that researchers want related to the research data being carried out. The subjects in this research were 12 students in class VIII. The data in this research was collected through test instruments in the form of initial tests and final tests and non-test instruments in the form of student worksheets (LKPD). The results of this research show that in the initial test, 12 (100%) students were in the failed qualification with an average achievement score of 13.8. The results of data analysis during the learning process show that the average achievement score for students' cognitive abilities is 90 with very good qualifications. The final test results showed that as many as 8 (66.7%) students were in very good qualifications, as many as 3 (25%) students were in good qualifications and as many as 1 (8.3%) students were in sufficient qualifications, with The average achievement score of students on the final test after the learning process is 87.62 with very good qualifications. For the N-Gain test results, the average student achievement score was 0.86 with high qualifications. Thus, it can be concluded that applying the guided inquiry model can increase mastery of energy material in class VIII students at SMP Negeri 60 Central Maluku.